Preparation of TiO2/VOx, TiO2/SiO2, and VOx/SiO2 nanostructures by hydrothermal methods and determination of their magnetic properties. (23rd January 2023) - Hasham, Mohammad Tamim Mohammad; Ay, Burak; Kaya, Dogan; Yildiz, Emel; Ekicibil, Ahmet
Abstract : New nanostructures of TiO2 /VO x, TiO2 /SiO2, and VO x /SiO2 have been prepared via hydrothermal methods at different temperatures and times. Abstract : New nanostructures of TiO2 /VO x, TiO2 /SiO2, and VO x /SiO2 have been prepared via hydrothermal methods at different temperatures and times. They were characterized using scanning electron microscopy-energy-dispersive X-ray spectroscopy, Fourier-transform infrared spectroscopy, and powder X-ray diffraction, whilst their magnetic properties were determined using a Physical Property Measurement System. According to the obtained results, the synthesized nanostructures can be used as magnetic detectors. The X-ray diffraction results for each titanium dioxide structure doped with vanadium or silica showed an increase the anatase structure. This proves that the photocatalytic properties of the synthesized nanostructures improve under optimum conditions. Temperature dependent magnetization ( M – T ) measurements were carried out for the composites under field-cooled and zero field-cooled conditions by applying a 500 Oe magnetic field. The M – T results indicate that all composites have weak ferromagnetic coupling, and they show a blocking temperature ( T B ), except for the TiO2 /VO x and SiO2 /VO x composites due to their strong paramagnetic signals. Magnetic field dependent magnetization ( M – H ) measurements were performed on the composites in fields up to ±6 T at 5, 40, 90, and 300 K. From the resulting hysteresis curves, it is observed that all composites show weak ferromagnetic behavior with a coercive field. The highest saturation magnetization ( M s ) and coercive field ( H c ) were found to be 0.963 emu g −1 and 764 Oe in the TiO2 /VO x composite at 5 K while a maximum M s of 0.126 emu g −1 is recorded for the composite with the formula Ti1.35 Si0 .32 O1.33 at room temperature.